How Talent Management and Career Development Significantly Influence Employee Turnover Intention - Sigit Bernanto; Rima Rahmayanti (Manunggal Halim Jaya, 2026)
Employee turnover remains a pressing issue in contemporary human resource management, even in organizations that provide a supportive and conducive work environment. This study is driven by the phenomenon in which employees working under relatively favorable conditions still develop the intention to leave and eventually resign to pursue better career opportunities elsewhere. Such turnover disrupts established teamwork and collaboration, as organizations must rebuild team dynamics with replacement employees, potentially reducing overall performance and productivity. This research therefore examines the influence of talent management and career development on employee turnover intention at PT X in Karawang. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to 75 employees consisting of professional staff, managerial, and executive-level employees. The data were analyzed using descriptive statistics and multiple linear regression with the assistance of SPSS (Statistical Package for the Social Sciences). The descriptive results indicate that talent management and career development at PT X are generally perceived as moderately effective. However, lower scores were identified in indicators related to the management of declining performance, clarity of job descriptions and performance standards, and transparency of short-term and long-term career paths. Employees also show a tendency to seek additional income or alternative employment opportunities. Hypothesis testing confirms that talent management and career development significantly affect turnover intention, both partially and simultaneously. The correlation coefficient (R) of 0.704 indicates a strong relationship, while the Adjusted R² of 0.482 shows that 48.2% of turnover intention is explained by the independent variables. These findings emphasize the importance of structured talent management and transparent career development systems in strengthening employee retention and sustaining organizational performance.